Parallel programming with CUDA for simulation of biochemical pathways - Anugerah Erlaut (2013)
Increasing amount of experimental data presents an opportunity for the modelling and simulation of biochemical pathways at increasingly larger scales. The time required to complete a simulation is proportional to the size of the model and dataset used for the simulation. Parallel programming enable the execution of program instructions in parallel, potentially reducing program execution time. This project is an interdisciplinary study assessing the feasibility of implementing parallel programming in the simulation of biochemical pathways. The CUDA parallel programming platform was used to implement the program. A program was written in CUDA C/C++ as a proof of concept. The program was tested using a glycolysis model described in another paper. The outcome of the test had not yet produced satisfactory result. This might be due to the incorrect calculation, or incorrect model recreation. Further study is necessary to confirm the case. However, the study had proved that it is possible to implement parallel programming for the simulation of biochemical pathways.